PENGARUH BRAND IDENTITY DAN CONTENT MARKETING TERHADAP BRAND AWARENESS LOCAL BRAND SKIN GAME PADA FOLLOWERS INSTAGRAM @SKINGAMEOFFICIAL - Brenda Pricillia Mariah (2022)
The COVID-19 pandemic is a momentum for increasing the digital economy and increasing online shopping trends. The trend of online shopping has an impact on the increasing number of online businesses where digital marketing competition is also getting tougher and more competitive. This study aims to analyze the effect of brand identity and content marketing on local brand awareness of the Skin Game brand on Instagram followers @skingameofficial. The research approach is an associative quantitative approach using a Google Form questionnaire distributed to 100 respondents who follow Instagram @skingameofficial. The sampling technique used was the Non-probability Sampling (Purposive Sampling) technique. Sources of research data include primary data and secondary data. Inferential statistical research analysis technique with the type of explanatory research. Based on the results of multiple linear regression tests, brand identity (X1) and content marketing (X2) have a positive influence on brand awareness (Y). The results of the correlation test showed a strong correlation level of 0.636. The result of the coefficient of determination test is 40.4%. The results of the T test show that there is an effect of each brand identity (X1) and content marketing (X2) on brand awareness (Y) and the results of the F test show that both X variables have a simultaneous effect on brand awareness (Y). This research proves the assumption of The Individual Differences Theory that audiences have their own personalities, selectively become media targets and pay attention to messages that are beneficial to their interests accompanied by individual responses. In this study, brand identity shows the characteristics of the Skin Game which is an attraction for respondents and content marketing @skingameofficial contains content with useful messages and motivates individuals to respect themselves more in accordance with the role of the Skin Game that supports self-realization. Brand identity and content marketing are unique for brands that affect brand awareness as a response that is tested in this study.